LINGUISTIC FOUNDATIONOF THE FORMATION OF BILINGUAL (ENGLISH-KARAKALPAK) DICTIONARY (Konferensiyalar | Conferences, 2024)
Dictionary usage is a way to express a society's culture, as well as its distinctive national characteristics and aspects of daily life. This article places particular emphasis on the need to create bilingual dictionaries for English and Karakalpak, taking into account their structural, social, and cultural purposes. The structure, techniques, and means of producing dictionaries, as well as research on the creation of the English-Karakalpak bilingual dictionary as one of the representations of the English and Karakalpak worlds, are all given specific emphasis in this study. Comparative analysis is the research's fundamental methodology. The study's findings show that each language's word systems have some commonalities and some differences.